Impact of self-funding on patient experience of oral anticoagulation self-monitoring: a qualitative study - Tompson, Alice (BMJ Open, 2016)
OBJECTIVE: To explore the impact self-funding has on patient experience of oral anticoagulation therapy self-monitoring. DESIGN: Semistructured, qualitative interviews were conducted. Transcripts were analysed thematically using constant comparison. SETTING: England. PARTICIPANTS: Interviewees were participants of the Cohort Study of Anticoagulation Self-Monitoring (CASM). Cohort members were recruited as they bought a monitor from the major manufacturer in the UK. A purposive sample was invited to be interviewed on completion of the 12-month cohort follow-up. DATA: Patient narratives on their experiences of self-monitoring their oral anticoagulation therapy in non-trial conditions. RESULTS: 26 interviews were completed. Interviewees viewed purchasing the monitoring device as a long-term commitment balancing the limitations of clinic-based monitoring against the cost. They were unable to try out the monitor prior to purchase and therefore had to be confident in their own ability to use it. The variable provision of self-monitoring equipment caused resentment, and interviewees were uncomfortable negotiating with healthcare professionals. High test strip usage while learning how to use the monitor caused anxiety that was exacerbated by worries about their cost. However, self-funding did mean that interviewees felt a sense of ownership and were determined to persevere to overcome problems. CONCLUSIONS: Self-funding has negative implications in terms of equity of access; however, the money invested acts as a barrier to discontinuation. If oral anticoagulation therapy self-monitoring devices and consumables were provided free of charge in routine care, the training and support available in England may need to be reviewed to prevent discontinuation rates rising to those observed in clinical trials.